Growth Media Conditions Influence the Secretion Route and Release Levels of Engineered Extracellular Vesicles. Issue 5 (21st November 2021) - Bost, Jeremy P.; Saher, Osama; Hagey, Daniel; Mamand, Doste R.; Liang, Xiuming; Zheng, Wenyi; Corso, Giulia; Gustafsson, Oskar; Görgens, André; Smith, CI Edvard; Zain, Rula; El Andaloussi, Samir; et al.
Abstract: Extracellular vesicles (EVs) are nanosized cell‐derived vesicles produced by all cells, which provide a route of intercellular communication by transmitting biological cargo. While EVs offer promise as therapeutic agents, the molecular mechanisms of EV biogenesis are not yet fully elucidated, in part due to the concurrence of numerous interwoven pathways which give rise to heterogenous EV populations in vitro. The equilibrium between the EV‐producing pathways is heavily influenced by factors in the extracellular environment, in such a way that can be taken advantage of to boost production of engineered EVs. In this study, a quantifiable EV‐engineering approach is used to investigate how different cell media conditions alter EV production. The presence of serum, exogenous EVs, and other signaling factors in cell media alters EV production at the physical, molecular, and transcriptional levels. Further, it is demonstrated that the ceramide‐dependent EV biogenesis route is the major pathway to production of engineered EVs during optimized EV‐production. These findings suggest a novel understanding to the mechanisms underlying EV production in cell culture which can be applied to develop advanced EV production methods. Abstract : Components of the cellular environment determine the quantity produced and the biogenesis of engineered extracellular vesicles (EVs). Cell media that contain serum alter EV production on several levels, including the biomolecular and transcriptional levels. Using serum‐free Opti‐MEM as an EV‐production media increases the quantity of engineered EVs produced in a ceramide‐dependent manner.